1984
DOI: 10.1111/j.1365-3024.1984.tb00801.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of protein restriction on the development of protective immunity to Leishmania mexicana

Abstract: Protein deprived C57BL/6 mice infected with 10(3) amastigotes of Leishmania mexicana showed early arrest of lesion progression during the first 5 weeks of infection with subsequent development of progressive non-healing lesions. In contrast, well nourished mice similarly infected developed gradual healing lesions. The early resistance of malnourished mice to 10(3) amastigotes was overcome by a larger dose. After a primary inoculation with 10(3) amastigotes protein deprived mice failed to express protective imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
(3 reference statements)
1
6
0
Order By: Relevance
“…In the present hamster model, chronic infection by L. infantum induced a decline in T-cell functionality similar in severity to that caused by protein malnutrition, but this condition plus infection dramatically reduced T cell functionality, as reported in a cutaneous leishmaniasis mice model [37]. The humoral immune response was also affected by protein malnutrition, manifested in the form of B cell depletion.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In the present hamster model, chronic infection by L. infantum induced a decline in T-cell functionality similar in severity to that caused by protein malnutrition, but this condition plus infection dramatically reduced T cell functionality, as reported in a cutaneous leishmaniasis mice model [37]. The humoral immune response was also affected by protein malnutrition, manifested in the form of B cell depletion.…”
Section: Discussionsupporting
confidence: 77%
“…Although Leishmania infection is known to impair the immune system [5], [36], only two studies have examined the adaptative immune response to Leishmania in conjunction with protein restriction. Malafaia et al [7] reported a reduction in IFN-γ production from SLA-stimulated splenocytes in malnourished mice infected with L. chagasi for 4 weeks, while Perez et al [37] found that protein-deprived mice infected with L. mexicana showed a depressed DTH response and a low in vitro splenic cell response to SLA and mitogens. In the present work, the 14%INF animals showed a patent specific cellular response, while the 3%INF animals showed an impaired response to leishmanial antigen and lower lymphocyte counts, particularly of CD4 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of CL, some studies have demonstrated the influence of PEM on the course of the disease (34–37). Pérez et al.…”
Section: Resultsmentioning
confidence: 99%
“…48 Studies from other groups confirm the influence of protein malnutrition on effective immune responses to Leishmania infection. 49 These authors used a diet with as little as 3% protein content, and the animals showed all the signs of malnutrition. In our model, dietary proteins were not simply removed or reduced; they were replaced by equivalent amounts of amino acids.…”
Section: Discussionmentioning
confidence: 99%